PVDF (Polyvinylidene Fluoride) super-hydrophobic membrane and preparation method thereof
The preparation of PVDF superhydrophobic membranes by the non-solvent composite spraying synergistic conversion method of nanoparticle, solved the problem that membrane distillation membranes are easily wetted during water treatment, achieved high throughput, high retention and anti-pollution properties, and promoted the industrial application of membrane distillation technology.
Patent Information
- Application Number
- CN202411760091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
AI Technical Summary
The existing membrane distillation membrane is easily wetted during water treatment, resulting in low water flux and membrane contamination, limiting its large-scale application in fields such as seawater desalination.
Using the nanoparticle non-solvent composite spray synergistic phase conversion method, an anti-pollution PVDF superhydrophobic membrane was successfully prepared. A multi-scale micro-nano structure was formed on the surface of the membrane, which improved the hydrophobicity and flux of the membrane while maintaining a high interception rate.
The high hydrophobicity of the membrane is achieved, which significantly improves the flux and salt retention of the membrane, reduces the risk of wetting and contamination of the membrane, and gives it a good application prospect in the fields of seawater desalination and other water treatment.
Smart Images

Figure CN119633607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a membrane material and a preparation method thereof, in particular to a PVDF super-hydrophobic membrane and a preparation method thereof, and belongs to the technical field of membranes. Background Art
[0002] Superhydrophobic material is a special wettability material, whose surface contact angle with water is greater than 150 degrees and whose rolling angle is less than 10 degrees, and has excellent waterproof performance. In nature, there are many superhydrophobic phenomena on certain parts of plants and animals such as lotus leaves, rose petals, fish scales, and butterfly wings. In 1997, Barthlott et al. observed the papillary micron-scale structure on the surface of lotus leaves for the first time through scanning electron microscopy. The superhydrophobicity and self-cleaning ability of the lotus leaf surface are actually derived from the combined effect of these papillary micron-scale structures and the surface nano-scale waxy substances. Inspired by this, scholars at home and abroad have paid extensive attention to hydrophobic surfaces and their preparation methods.
[0003] Studies have found that reducing surface energy and constructing high-roughness structures are the two main ways to prepare hydrophobic surfaces. Common preparation methods include layer-by-layer self-assembly, physical or chemical vapor deposition, etching, template, electrostatic spraying, and sol-gel methods. Superhydrophobic materials have potential application value in many fields due to their waterproof, anti-corrosion, anti-icing and self-cleaning properties, including but not limited to construction, textiles, medical, anti-fouling coatings, oil-water separation, sensors, wearable devices, etc. Membrane distillation (MD) technology is an emerging membrane separation technology based on the above-mentioned hydrophobic materials with hydrophobic microporous membranes as the main body. This technology combines membrane and thermal methods. Because its theoretical retention rate is 100%, the application process has low temperature and pressure requirements, and waste heat can be recycled, it is considered to be a technology suitable for water treatment. However, to date, this technology has not yet been industrialized, mainly because there are relatively few membrane materials suitable for membrane distillation processes.
[0004] As the separation medium between the feed side and the permeate side, the membrane distillation membrane mainly functions to separate the different components contained in the feed. It faces two main problems in the application process: low water flux and membrane wetting. Since the membrane is in direct contact with the liquid feed during the separation process and serves as a transmission channel for steam, the biggest problem faced by the microporous membrane is that it is easy to be wetted, which limits the large-scale application of membrane distillation in water treatment fields such as seawater desalination. In summary, the membrane distillation membrane has the following requirements: 1) The membrane is not wetted, and capillary condensation does not occur in the membrane pores to ensure high hydrophobicity; 2) It has a porous structure with high porosity; 3) Maintain good thermal stability and chemical stability; 4) It can achieve high flux and high retention in the MD process. As mentioned above, the biggest problem faced in the application of membrane distillation is membrane wetting and membrane fouling. Therefore, the most important feature of the MD membrane is porous hydrophobicity. In-depth research on hydrophobic membranes is the key to promoting the application of the MD process.
[0005] In view of the above reasons, the development and modification of highly hydrophobic membrane distillation membrane materials are undoubtedly the focus of research attention. It is urgent to develop a pollution-resistant super-hydrophobic membrane with simple process and suitable for stable operation of MD. Summary of the invention
[0006] To address the deficiencies of the prior art, one of the purposes of the present invention is to provide an anti-pollution PVDF super-hydrophobic membrane; a second purpose is to provide an innovative preparation method for the membrane: a nanoparticle non-solvent composite spray synergistic phase inversion method.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention first discloses a method for preparing a PVDF super-hydrophobic membrane, which is a unique and creative nanoparticle non-solvent composite spray synergistic phase transformation method independently developed by the applicant, and specifically comprises the following steps:
[0009] S1. Preparation of modified SiO 2 Nanoparticles: First, the hydrophilic silica nanoparticles are dispersed in a solvent, stirred and ultrasonically dispersed to form a suspension, the stirring speed is 100-800 rpm, and the stirring time and ultrasonic dispersion time are both 1-30 min; then, sodium methyl silicate is added to the suspension and stirred, and then PFDTES and TEOS are added thereto, mechanically stirred, reacted at 10-60°C for a period of time, and hydrolyzed and co-condensed to obtain the modified hydrophobic F-SiO 2 The nanoparticles are washed and dried for later use, the drying temperature is 25 to 80° C., and the drying time is 1 to 24 hours;
[0010] S2. Prepare PVDF casting solution: dry PVDF powder, mix with solvent TEP, seal and put into an oven, shake the casting solution in time to ensure uniform dissolution, until a uniform and transparent casting solution is obtained;
[0011] S3, preparing spraying liquid: adding a certain amount of modified F-SiO 2 The powder was evenly dispersed in anhydrous ethanol, ultrasonicated for 30 min, and oscillated for another 5 s using a mixer before spraying to ensure a uniform solution;
[0012] S4, preparation of PVDF super-hydrophobic membrane: casting the casting liquid of step S2 on a non-woven fabric and scraping to obtain a new membrane, the scraper gap is 250 μm, and then immediately spraying the spraying liquid prepared in step S3 onto the surface of the new membrane with a spray gun, and controlling the spraying amount by controlling the number of spraying times, immersing the sprayed membrane in a deionized water coagulation bath at room temperature for at least 12 hours to complete the phase inversion process, and finally drying under ambient conditions to obtain the PVDF super-hydrophobic membrane.
[0013] Preferably, in the aforementioned step S1, the solvent is a mixed solvent of water and ethanol, and the volume ratio of water to ethanol is 1:(2-50).
[0014] More preferably, in the aforementioned step S1, the usage ratio of the silica nanoparticles, sodium methyl silicate, PFDTES and TEOS is (1-10):(1-10):(1-10):(1-10), wherein the silica nanoparticles and sodium methyl silicate are parts by weight, and PFDTES and TEOS are parts by volume.
[0015] More preferably, the mass ratio of the PVDF powder to the TEP solvent (solvent triethyl phosphate) is 1:(3-10).
[0016] Further preferably, in the aforementioned step S3, the mass percentage of the modified nanoparticles in the spraying liquid is 0.1% to 1.5%.
[0017] Further preferably, the aforementioned spraying liquid comprises four kinds, wherein the mass percentages of the modified nanoparticles are 0.1wt%, 0.5wt%, 1.0wt% and 1.5wt% respectively.
[0018] Further preferably, in the aforementioned step S4, the spray gun is connected to a small air pump to perform a spraying operation at a working pressure of 2 bar.
[0019] Further preferably, the modified F-SiO prepared in the above step S1 2 The water contact angle is higher than 150°.
[0020] The present invention also discloses a PVDF super-hydrophobic membrane, which is prepared by the non-solvent composite spray coordinated phase transformation method as described above.
[0021] Preferably, the surface of the PVDF super-hydrophobic membrane has high roughness and low surface energy, a water contact angle of 150.75°, a maximum salt retention rate of 99.99%, and a flux of 18.21 kg·m -2 ·h -1 above.
[0022] The present invention is beneficial in that:
[0023] (1) The present invention uses sodium methyl silicate, perfluorodecyl triethoxysilane (PFDTES) and tetraethoxysilane (TEOS) as catalysts / reactants to successfully achieve hydrophilic SiO 2 Fluorinated hydrophobic modification of nanoparticles. In view of the harmfulness of traditional spray liquids to the human body and the environment, sodium methyl silicate is used as a raw material in this application, which can be used as both a reactant and an alkaline catalyst to replace the ammonia water with a pungent odor in the traditional silane hydrolysis and condensation. In addition, studies have shown that the addition of a small amount of TEOS also helps the hydrolysis and condensation of PFDTES on the surface of nanoparticles, which can further enhance the modified F-SiO 2 Super hydrophobicity.
[0024] (2) This invention innovatively proposed for the first time a nanoparticle non-solvent composite spray synergistic phase transformation method, which successfully transformed F-SiO 2 Compounded to the membrane surface, a multi-scale micro-nano structure is formed on the membrane surface, including micron-scale mesh roughness and nano-scale roughness formed by nanoparticles. These structures improve the hydrophobicity of the membrane surface while giving the membrane structure better flux and good interception rate, and finally obtain a PVDF super-hydrophobic membrane with excellent performance and anti-pollution. Moreover, the process of the present invention has the advantages of being simple and efficient, and no additional treatment is required after the membrane is formed, and it has a good prospect for industrial application.
[0025] (3) With the increase of the content of nanoparticles in the spraying liquid, the nanoparticles gradually covered the inherent reticular macroporous structure of the sprayed ethanol membrane in the membrane surface morphology, the structure gradually became uniform, and the membrane cross-sectional morphology hardly changed; at the same time, the water contact angle of the membrane surface became larger, the roughness became larger, the hydrophobicity gradually improved, and the high hydrophobicity was maintained in boiling water for more than 6 hours. With the increase of the content of sprayed nanoparticles, the membrane porosity decreased slightly, the bubble point pore size first increased and then decreased, the pore size structure became larger as a whole, and the liquid penetration pressure of the membrane continued to rise.
[0026] (4) These membranes were applied to 3.5wt% high-salt VMD test. With the increase of nanoparticle content in the spray solution, the flux increased first and then decreased, and the salt retention rate gradually increased. When the nanoparticle content in the non-solvent spray was 1.5wt%, the obtained super-hydrophobic membrane had a maximum surface contact angle of 150.75° and an LEP value of 2.50bar, which was very helpful to improve the membrane performance. The maximum salt retention rate reached 99.99% and the flux could reach 18kg·m -2 ·h -1 The above performance indicators are better than those of the base membrane without nanoparticles and the membrane prepared by the traditional non-solvent induced phase separation method.
[0027] (5) Further long-term membrane distillation experimental results show that: after 50 hours of long-term operation, the membrane flux slowly decreases, the retention rate remains at a high level, and the recovery effect is very good after water washing, which shows that the anti-pollution performance of the superhydrophobic membrane of the present invention is very excellent, which makes it have good application prospects in the fields of seawater desalination, brackish water treatment, food concentration, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 SiO 2 and F-SiO 2 Infrared spectrum of powder;
[0029] Figure 2 The infrared spectra of the films (S0-S4) of Comparative Example 1 and Examples 1-4 are shown;
[0030] Figure 3 SiO 2 and F-SiO 2 X-ray photoelectron spectroscopy of powder (a), F-SiO 2 High-resolution C1s spectrum (b) and high-resolution F1s spectrum (c) of the powder;
[0031] Figure 4 The scanning electron microscope energy spectrum of the film products (S0-S4) of Comparative Example 1 and Examples 1-4;
[0032] Figure 5 SiO 2 and F-SiO 2 Comparison chart of hydrophilicity and hydrophobicity of powders;
[0033] Figure 6 It is a water contact angle test data diagram of the membrane products (S0-S4) of Comparative Example 1 and Examples 1-4;
[0034] Figure 7 The data diagram of the membrane water contact angle of Comparative Examples 2 to 4, Example 1 and Example 4;
[0035] Figure 8 The scanning electron microscope images of the membrane products of Comparative Example 1 and Examples 1 to 4 are shown, wherein (a) is the S0 membrane sprayed with ethanol, (b) to (e) are the F-SiO membrane sprayed with 2 S1-S4 films with nanoparticle contents of 0.1wt%, 0.5wt%, 1.0wt%, and 1.5wt% respectively;
[0036] Fig. 9 The scanning electron microscope images of the membrane products of Comparative Examples 2 to 4, Examples 1 and 4, wherein (a) is the PVDF base membrane C0 membrane, (b) to (c) are the C1 membrane and the C2 membrane, respectively, and (d) to (e) are the sprayed F-SiO 2 S1 and S4 films with nanoparticle contents of 0.1 wt% and 1.5 wt%, respectively;
[0037] Fig.10 The cross-sectional scanning electron microscope images of the membrane products of Comparative Example 1 and Example 4, wherein (a) is the S0 membrane and (b) is the S4 membrane;
[0038] Fig.11 The roughness and topological structure diagram of the sprayed S0-S4 film;
[0039] Fig.12 This is a comparison of the base film and S4 film prepared by the NIPS method after being immersed in dyes;
[0040] Fig.13 The average pore size and bubble point pore size diagram of S0~S4 membranes;
[0041] Fig.14 The porosity and liquid penetration pressure data of S0~S4 membranes are shown in FIG.
[0042] Fig.15 Schematic diagram of the vacuum membrane distillation test device.
[0043] Fig.16 The water contact angle change diagram of S4 film after immersion in boiling water;
[0044] Fig.17 The figure shows the change of vacuum membrane distillation flux and salt rejection rate of S0~S4 membranes;
[0045] Fig.18 The graphs of the changes in vacuum membrane distillation flux and salt rejection rate of C0, C1, C2, S1 and S4 membranes;
[0046] Fig.19 The long-term vacuum membrane distillation performance change diagram of S3, S4 and C0 membranes;
[0047] Fig. 20The scanning electron microscope images of the membrane surface of S3 membrane (a) before vacuum membrane distillation test, after 10 hours of vacuum membrane distillation test and after 10 hours of test and water circulation cleaning, (b) the flux and retention rate data diagram at the beginning of vacuum membrane distillation, after 10 hours and after 10 hours of test and water circulation cleaning; DETAILED DESCRIPTION
[0048] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] In the present invention, unless otherwise specified, all raw materials used are commercially available, and preferred commercial sources are shown in Table 1 below.
[0050]
[0051] Table 1 Sources of reagents and materials used in the present invention
[0052] Examples 1 to 4 of the present invention adopt an innovative process: nanoparticle non-solvent composite spray synergistic phase transformation method to prepare membranes S1-S4. The method steps are basically similar, and the main difference lies in the specific process parameters and the F-SiO in the spraying liquid. 2 Differences in the mass percentage of nanoparticles.
[0053] Example 1
[0054] The specific preparation method of this embodiment comprises the following steps:
[0055] (1)SiO 2 Hydrophobic modification of nanoparticles (fluorination modification)
[0056] First, 0.5 g of hydrophilic silica nanoparticles (30 nm) were dispersed in a 50 mL water / ethanol (volume ratio of 1:10) mixture, stirred at 500 rpm for 10 min, and ultrasonically dispersed for 10 min. 0.5 g of sodium methyl silicate was added to the suspension and stirred for 10 min. Then, 0.6 mL of PFDTES and 0.15 mL of TEOS were added with a pipette and mechanically stirred for 2 h to prepare hydrophobic F-SiO 2 Nanoparticles. The F-SiO 2 The dispersion was centrifuged at 8000 rpm for 10 min, the supernatant was removed and washed with anhydrous ethanol, the centrifugation operation was repeated three times, and the dispersion was dried in a vacuum drying oven at 40° C. overnight for use.
[0057] (2) Preparation of PVDF casting solution
[0058] Place the PVDF powder in a vacuum drying oven at 120°C for 24 hours for drying. Mix the dried PVDF powder and solvent TEP in a reagent bottle at a mass ratio of 14:86, seal and place in a 90°C oven, shake the casting solution in time to ensure uniform dissolution, until a uniform and transparent casting solution is obtained, and cool the casting solution to 25°C before scraping.
[0059] (3) Preparation of spray liquid
[0060] A certain amount of modified F-SiO prepared in step S1 is added 2 The powder was evenly dispersed in anhydrous ethanol, wherein the nanoparticle content was 0.1 wt %, and ultrasonicated for 30 min. A mixer was used to oscillate for another 5 s before spraying to ensure a uniform solution.
[0061] (4) Preparation of PVDF flat membrane
[0062] First, the casting solution was cast on a non-woven fabric (20×15 cm 2 ) on the surface of the new membrane, the scraper gap is 250μm, and then a certain amount of spraying liquid (prepared in step (3)) is immediately sprayed onto the surface of the new membrane with a spray gun. The spraying amount is controlled by controlling the number of spraying. The spray gun needs to be connected to a small air pump to perform the spraying operation at a working pressure of 2bar. The sprayed new membrane is immersed in a deionized water coagulation bath at room temperature for at least 12h to complete the phase inversion process. Finally, the PVDF membrane is dried under ambient conditions and recorded as membrane S1.
[0063] Example 2
[0064] The process steps of Example 2 are the same as those of Example 1, the main difference being that in step (3), the content of the nanoparticles is 0.5 wt%. The prepared membrane is recorded as membrane S2.
[0065] Example 3
[0066] The process steps of Example 3 are the same as those of Example 1, the main difference being that in step (3), the content of the nanoparticles is 1.0 wt%. The obtained membrane is recorded as membrane S3.
[0067] Example 4
[0068] The process steps of Example 4 are the same as those of Example 1, the main difference being that in step (3), the content of the nanoparticles is 1.5 wt%. The prepared membrane is recorded as membrane S4.
[0069] Comparative Example 1
[0070] The specific process of this comparative example is:
[0071] (1) Preparation of PVDF casting solution
[0072] Place the PVDF powder in a vacuum drying oven at 120°C for 24 hours for drying. Mix the dried PVDF powder and solvent TEP in a reagent bottle at a mass ratio of 14:86, seal and place in a 90°C oven, shake the casting solution in time to ensure uniform dissolution, until a uniform and transparent casting solution is obtained, and cool the casting solution to 25°C before scraping.
[0073] (2) Preparation of PVDF flat membrane
[0074] First, the casting solution was cast on a non-woven fabric (20×15 cm 2 ) with a scraper gap of 250 μm, and then immediately spray anhydrous ethanol (without nanoparticles) onto the surface of the new membrane with a spray gun. The sprayed new membrane was immersed in a deionized water coagulation bath at room temperature for at least 12 h to complete the phase inversion process. Finally, the PVDF membrane was dried under ambient conditions and recorded as membrane S0.
[0075] Comparative Examples 2, 3 and 4 all used the traditional non-solvent induced phase separation method (NIPS) to prepare membrane products C0-C2 in order to explore the effects of different process methods on the performance of membrane products.
[0076] Comparative Example 2
[0077] The specific process of this comparative example is:
[0078] (1) Preparation of PVDF casting solution
[0079] Place the PVDF powder in a vacuum drying oven at 120°C for 24 hours for drying. Mix the dried PVDF powder and solvent TEP in a reagent bottle at a mass ratio of 14:86, seal and place in a 90°C oven, shake the casting solution in time to ensure uniform dissolution, until a uniform and transparent casting solution is obtained, and cool the casting solution to 25°C before scraping.
[0080] (2) Preparation of PVDF flat membrane
[0081] The casting solution was cast on a non-woven fabric (20×15cm 2 ) with a scraper gap of 250 μm, immersed in a deionized water coagulation bath for at least 12 h, and then dried, and then anhydrous ethanol was sprayed on the dried PVDF membrane surface. Finally, the PVDF membrane was dried under ambient conditions and recorded as membrane C0.
[0082] Comparative Example 3
[0083] In this comparative example, steps (1) to (3) are the same as those of Examples 1-4, with the main difference being step (4): first, the PVDF casting liquid is scraped and immersed in a deionized water coagulation bath for at least 12 hours, followed by drying, and then a certain amount of 0.1 wt% nanoparticle spray liquid is sprayed onto the surface of the dried PVDF base membrane (this method is a traditional non-solvent induced phase separation method). The resulting membrane is denoted as C1.
[0084] Comparative Example 4
[0085] The main difference between this comparative example and comparative example 3 is that the mass percentage of nanoparticles in the nanoparticle spraying liquid is 1.5wt%, and the prepared film is recorded as C2.
[0086] Structural characterization
[0087] (1) Fourier transform infrared spectroscopy (FTIR)
[0088] The infrared spectrometer (Nicolet IS10, Thermofisher, USA) was used to analyze the -1 The scanning range of hydrophilic SiO 2 and hydrophobic F-SiO 2 Characterization and analysis of the chemical composition of nanoparticles; at 4000-600cm -1 The scanning range of ethanol spray film and F-SiO 2 The nanoparticle composite spray film was characterized by infrared.
[0089] Figure 1 The infrared spectrum is shown. It can be seen from the figure that SiO 2 and F-SiO 2 The powders have a common -1 and 804cm -1 The stretching vibration peak of Si-O-Si is located at 2 The powder has several new obvious peaks: 1238cm -1 、1200cm -1 and 678cm -1 -CF 2 -and-CF 3 The characteristic peaks of the groups indicate that hydrophobic groups are grafted onto the surface of the silica nanoparticles, proving that SiO 2 Successfully modified by fluorination.
[0090] The modified F-SiO 2 After the powder is formed, the membrane is prepared by the nanoparticle non-solvent composite spray synergistic phase transformation method invented by the present invention. Then, the chemical structure of the super hydrophobic membrane is analyzed by FTIR. Figure 2As shown, the amorphous peaks of PVDF are 872, 1064, 1180 and 1404 cm -1 872 and 1404 cm -1 The strong absorption peak at -CH 2 stretching vibration of the group, and 1180cm -1 The absorption peaks at 845, 1102, and 1320 cm-1 in the infrared spectra of membranes S1 to S4 were increased compared with those of membrane S0. -1 The absorption peaks correspond to the characteristic peaks of silicon-oxygen bonds and silicon-carbon bonds, 1064 to 1180 cm -1 The wide range of peaks between 2 and 3 is also caused by the stretching vibration of Si-O-Si bonds.
[0091] The FTIR results confirm that the hydrophobic F-SiO 2 The nanoparticles were successfully compounded onto the surfaces of the membranes S1 to S4 by the non-solvent composite spray coordinated phase inversion method of the present invention.
[0092] (2) X-ray photoelectron spectroscopy (XPS)
[0093] The SiO2 before and after modification was tested by X-ray photoelectron spectrometer (PHI 5000VersaProbeⅢ, ULVAC-PHI, Japan). 2 Powder elemental composition.
[0094] Figure 3 XPS spectra, where (a) is the original hydrophilic SiO 2 And modified F-SiO 2 The XPS spectrum shows that: F-SiO 2 The F1s peak (688 eV) is increased and the C1s peak (291 eV) intensity is increased. Combined with Table 2 below, the C / O / F / Si atomic ratio is 3.70 / 2.10 / 4.22 / 1, of which the F content is as high as 38.31%, which indicates that the modified SiO 2 There are a lot of -Si(CH 2 ) 2 (CF 2 ) 7 CF 3 Group. Figure 3 As shown in (b) and (c), by 2 The high-resolution XPS data of the C1s and F1s peaks of the nanoparticles were analyzed to confirm the presence of -CF 2 -and-CF 3 Group, C 1s peak distribution in CF 3 (293.3eV), CF 2(291.2eV) and CC / CH / C-Si (284.8eV), the F 1s peak is distributed in CF 3 (688.2eV) and CF 2 (689.2eV), which further proves that the modified SiO 2 The composition of the nanoparticles changes, indicating that PFDTES 2 The surface was effectively grafted.
[0095] element content(%) C 33.55 O 19.07 F 38.31 Si 9.07
[0096] Table 2F-SiO 2 Chemical composition of powder
[0097] (3) Energy dispersive spectrometry (EDS)
[0098] An energy spectrometer (XFlash 6130, BRUKER, USA) was used in conjunction with a scanning electron microscope (SEM) to analyze and determine the distribution of C, F, O and Si elements on the surface of the sprayed film samples.
[0099] The elemental composition of the surface of the prepared original S0 film and the modified nanoparticle S1~S4 film was analyzed by SEM-EDS. Figure 4 As shown in Figure 2, the analysis results show that the surfaces of the prepared original S0 film and the sprayed nanoparticle film are mainly composed of C, F and O elements. EDS elemental analysis confirmed that SiO 2 Nanoparticles, which is consistent with the SEM images to be analyzed later and the FTIR results analyzed previously.
[0100] By analyzing Figure 4 From the element composition table in the spray liquid, it can be seen that as the content of nanoparticles in the spray liquid increases from 0.1wt% to 1.5wt%, the mass fraction and atomic percentage of Si element on the film surface gradually increase, which indicates that SiO 2 The composite amount of nanoparticles on the membrane surface increases with the increase of spraying amount.
[0101] (4) Contact angle
[0102] The water contact angle was tested using a contact angle analyzer (OCA-15EC, Dataphysics, Germany). The test method was as follows: operate the measuring instrument to drop 1.0 μL of water on the surface of the tablet, then immediately take a static surface contact picture and measure the contact angle.
[0103] SiO 2 and F-SiO 2 The two powders were pressed into tablets to test the water contact angle of the powders. It can be seen that Figure 5 (a) Hydrophilic SiO before modification2 The contact angle of the modified F-SiO 2 The water contact angle was 155.5°, achieving a hydrophilic-hydrophobic transition. At the same time, the two powders were poured into clean water and ultrasonicated for 10 minutes. 2 The powder completely floats on the water surface, while the original SiO 2 The powder sinks to the bottom of the water, e.g. Figure 5 As shown in (b), this self-floating property is an intuitive manifestation of hydrophobicity, which further indicates that PFDTES and sodium methyl silicate have successfully hydrophobically modified silica nanoparticles.
[0104] Figure 6 The water contact angle test results of membranes S0 to S4 are shown in the figure. As shown in the figure, with the increase of the amount of nanoparticles sprayed, the water contact angle of the sprayed membrane can reach up to 150.75°, reaching the super hydrophobic index. Corresponding to the SEM image, the water contact angle of the membrane increases with the increase of the amount of F-SiO 2 However, when the content of nanoparticles in the spraying liquid is too high, the spraying equipment will be blocked, affecting the spraying effect. Therefore, the present invention sets the maximum content of nanoparticles to no more than 1.5wt%.
[0105] In spraying F-SiO 2 After the nanoparticles are added, a multi-level micro-nano rough structure will be formed on the membrane surface. The roughness increases, which makes the contact area between the membrane surface and water larger, so the water contact angle shows an upward trend. In addition, the membrane surface is covered with F-SiO 2 Nanoparticles, SiO 2 The fluorination modification makes the carbon fluorine molecular chain grafted on the surface of the nanoparticles, which is exposed on the surface of the membrane, greatly reducing the surface energy, so that the adhesion of the membrane surface is poor, which is conducive to improving the hydrophobicity of the membrane surface. It can be seen that in the present invention, the applicant adopts the original nanoparticle non-solvent composite spray synergistic phase transformation method, which simultaneously improves the surface roughness of the membrane and reduces the surface energy of the membrane, so that the PVDF membrane achieves a super hydrophobic effect.
[0106] Figure 7 The water contact angle test diagram of membranes C0 to C2 shows that the base membrane C0 has the smallest water contact angle, indicating that its hydrophobicity is the worst. Compared with the nanoparticle composite spray membranes of Examples 1 to 4, the C1 and C2 membranes (Comparative Examples 3 to 4) obtained by directly spraying nanoparticles on the dry base membrane have larger water contact angles, up to 157.7°, reflecting better hydrophobicity. This is because the nanoparticles stay on the surface of the membrane when sprayed directly on the dry base membrane; as the spraying concentration increases, the hydrophobic F-SiO 2The nanoparticle composite spray film presents a bicontinuous polymer network structure. Under pressure spraying, some nanoparticles enter the polymer network and do not just stay on the surface of the film. The membranes S4 and C2 prepared in Example 4 and Comparative Example 4 at a spray concentration of 1.5wt% both achieve super hydrophobicity.
[0107] (5) SEM characterization
[0108] Scanning electron microscope SEM (SUPRATM55, Zeiss, Germany) was used to characterize the surface and cross-sectional morphology of the membrane. The membrane surface samples needed to be dried in an oven at 60°C for 10 h in advance, and the cross-sectional samples needed to be cut with liquid nitrogen. The samples were then glued to the sample stage and sprayed with gold for 70 seconds using an automatic precision coating machine (Q150R ES, America) before SEM testing. Image J software was used to measure the thickness of the separation layer of the membrane cross section, and each group was measured multiple times to obtain accurate values.
[0109] like Figure 8 As shown in the figure, compared with the surface morphology of the S0 film in comparative example 1, after spraying the nanoparticles, the surfaces of the films S1 to S4 not only maintain a double continuous network structure, but also composite F-SiO 2 Nanoparticles form a micro-nano multi-level composite structure. As the amount of spraying increases, the area of the film surface covered with nanoparticles increases, and the structure distribution becomes more uniform. 2 After that, the macropores connected by polymer fibers on the surface of S1 membrane were larger and more loose than those of S0 sprayed with ethanol alone. The applicant analyzed that this might be because when ethanol was sprayed alone, the density of ethanol was smaller and the impact force of spraying on the membrane surface was smaller. 2 After the addition of nanoparticles, the impact of the spraying liquid is enhanced, which has a greater impact on the macroporous structure formed on the membrane surface. However, under the magnification, since the main body of the spraying liquid is still ethanol, the effect of the non-solvent itself on the membrane phase transformation process has not changed, so the formed bicontinuous pore structure has not changed. After the content of spraying nanoparticles increases, the macroporous structure on the membrane surface is covered by nanoparticles and the pore size becomes smaller, which may reduce the flux of membrane distillation. If the F-SiO 2 If the content of nanoparticles is too low, the effect on surface roughness is small and the improvement of hydrophobicity is limited. Therefore, the amount of nanoparticles added can directly affect the hydrophobicity of the membrane surface.
[0110] like Fig. 9As shown, the surface of the dried PVDF base film (C0) is smooth, and uniform small holes can be seen on the surface. Using the traditional preparation method, after spraying the nanoparticles, the presence of nanoparticles can be directly observed on the membrane surface. The aggregation morphology of the surface is different with the addition amount of nanoparticles. When the addition amount is 0.1wt% (C1), the nanoparticles cannot completely cover the membrane surface, there are certain gaps, and part of the surface shows the morphology of the base film (C0). As the amount of nanoparticles added increases, the nanoparticles of the C2 membrane almost completely cover the membrane surface, and the distribution is relatively uniform and dense.
[0111] Furthermore, the structure of the internal cross section of the film after spraying the nanoparticles was observed, such as Fig.10 As shown, the S0 membrane of comparative example 1 and the S4 membrane of embodiment 4 both have a sponge-like cross-sectional structure, and there is no obvious change in the structure. It can be seen that whether nanoparticles are added to the spraying liquid does not affect the internal pore structure of the membrane.
[0112] (6)Surface characteristics
[0113] The topological structure of the membrane surface was characterized by atomic force microscopy AFM (Dimension FastScan, Bruker, Germany). The membrane sample was cut into a square and fixed on the operating table. The AFM software was turned on and the ScanAsyst mode was used for testing. The scanning size was 5 μm × 5 μm. The Nanoscope Analysis software was used for data processing to obtain different roughness values.
[0114] Fig.11 The roughness change diagram of films S0 to S4 is shown. It can be seen that after adding nanoparticles to the spraying liquid, the roughness increases, which is consistent with the change trend of the water contact angle. 2 As the content of nanoparticles increases, they gradually accumulate on the membrane surface, forming a multi-layered micro-nano rough structure. The surface roughness R of the S4 membrane a As high as 303.3nm, the increase in roughness further enhances the hydrophobicity of the membrane material.
[0115] Similarly, the super-hydrophobic film can also show good hydrophobicity in dye aqueous solution. Fig.12 As shown in the figure, the membranes C0 and S4 prepared by the NIPS method were immersed in direct light-fast turquoise dye, and the membrane S4 showed obvious superhydrophobicity. The control membrane C0 on the left was slightly stained, while the S4 membrane was bent downward when immersed in the dye aqueous solution and was not stained with dye. After being immersed and taken out, the membrane surface did not change color, which was in sharp contrast to the control membrane C0. This phenomenon is mainly because the surface of the S4 membrane is a high-roughness structure at the micro-nano level, which causes "cavitation" on the solid-liquid contact surface, forming a layer of air film between the water and the membrane surface, so it can not be stained in the dye.
[0116] From the above, we can see that by spraying modified nanoparticles, the surface roughness of the membrane increases and the hydrophobicity improves. However, we know that the agglomeration of nanoparticles will block the membrane pores and have a certain impact on the pore size structure of the membrane surface. Fig.13 As shown in the figure, the bubble point pore size of the sprayed film increases first and then decreases with the increase of nanoparticle content. This is because when the SiO content of 0.1wt% and 0.5wt% is sprayed 2 When the droplets containing agglomerated nanoparticles are sprayed onto the membrane surface, the impact is greater and the pore size is larger. This agglomeration phenomenon has also been verified in the aforementioned SEM test. 2 When the content is further increased to 1.0wt% and 1.5wt%, a large number of nanoparticles cover the membrane pores, and the membrane pore size decreases, but the bubble point pore size is still larger than that of the S0 membrane sprayed with ethanol only. As can be seen from the figure, the average pore size of the S1~S4 membranes is also larger than that of the S0 membrane, that is, the pore size of the membrane sprayed with nanoparticles is larger than that of the membrane sprayed with ethanol only, which has a crucial impact on the flux and other properties to be described later.
[0117] Performance Testing
[0118] Fig.14 The porosity and LEP test data of the membrane are shown (LEP is the liquid penetration pressure, which refers to the pressure that will make the liquid completely penetrate the membrane into the permeate side and wet the membrane). Due to the increase of sprayed nanoparticles, the porosity decreases with the increase of content. After the spray content increases to 1.5wt%, the porosity decreases from 86.44% of S1 to 75.05% of S4. The decrease in porosity is because the pores in the bicontinuous polymer network structure of the membrane become smaller after being covered with nanoparticles. This is Figure 8 It is also reflected in the SEM image, but when the content of nanoparticles in the spraying liquid is low, the change in porosity is not obvious. The change trend of LEP data is opposite to that of porosity. It increases with the increase of the content of sprayed nanoparticles. LEP data is the result of the combined effect of pore structure and hydrophobicity. Compared with S0 membrane, the average pore size of S1 membrane increases from 0.236μm to 0.370μm, the bubble point pore size increases significantly, the porosity is smaller, and the water contact angle is slightly larger. A combination of various factors causes the LEP value of S1 membrane to drop significantly, while the LEP of S4 membrane increases to 2.50bar, which is basically the same as S0 membrane. This is because its super hydrophobicity plays a major role. The membrane pores are less likely to be penetrated by liquids, which offsets the effect of the larger pore structure.
[0119] Vacuum membrane distillation (VMD) test equipment such as Fig.15 As shown, the effective area of the membrane sample is 35.26 cm 2, installed in the membrane pool. The feed is 3.5wt% sodium chloride solution (conductivity is 53.0±1.8mS·cm -1 ), the temperature is maintained at 60℃. The permeate side pressure is maintained at 1-3kPa by a vacuum pump. The permeate vapor is condensed and collected in a liquid nitrogen cold trap. Finally, the mass and conductivity of the permeate are measured. The flux (J) and retention rate (R) are calculated by formulas (1-1) and (1-2), respectively:
[0120]
[0121] Where J represents the vacuum membrane distillation flux (kg·m- 2 ·h -1 ), Δm (kg) represents the mass increase of the permeate in a certain period of time, t (h) represents the sample collection time, A (m 2 ) represents the membrane sample area; R represents the retention rate of the membrane, C p and C f are the salt concentrations of the permeate and feed solutions, respectively.
[0122] When performing vacuum membrane distillation, the feed liquid is generally a high-temperature solution. Therefore, the stability of the super-hydrophobic membrane in a high-temperature environment is also very important. To test this performance, the membrane S4 was immersed in 95°C hot water for a period of time to test the change in the water contact angle. Fig.16 As shown, after soaking in high-temperature hot water for 1 hour, the water contact angle decreases. As the soaking time increases, the water contact angle slowly decreases to about 140° and remains stable. This shows that the membrane prepared by the present invention can still maintain high hydrophobicity in a long high-temperature environment.
[0123] The membrane was tested for 3.5 wt% vacuum membrane distillation. Fig.17 As shown in the figure, the VMD steam flux of nanoparticle composite spray membranes S1 to S4 is larger than that of S0 membrane. As the content of nanoparticles increases, the flux of the membrane decreases, which is consistent with the LEP trend, but the salt rejection rate gradually increases. The flux of S0 membrane is 19.48 kg·m -2 ·h -1 , while the membrane flux of S1 increased to 26.69 kg·m -2 ·h -1 This is because the membrane pore size of the sprayed nanoparticle membrane becomes larger (as mentioned above), the membrane thickness becomes smaller, and the mass transfer resistance of the membrane becomes smaller, so the flux increases. However, due to the low hydrophobicity of the membrane and the poor uniformity of the membrane surface structure, the salt retention rate of the S1 membrane is relatively low, only 98.2%. When the nanoparticle content increases to 1.5wt%, the flux decreases slightly to 18.21kg·m -2 ·h -1, but the salt rejection rate increased to 99.99%. It can be seen that the reduction of membrane pore size and the increase of membrane thickness are not conducive to the improvement of membrane distillation flux, while the improvement of hydrophobicity and the uniformity of morphology are conducive to the improvement of salt rejection rate.
[0124] Although the hydrophobicity of membranes C1 and C2 is better, their VMD fluxes are much lower than those of nanoparticle composite spray membranes S1 to S4, e.g. Fig.18 The applicant analyzed that this is because: membranes C1 and C2 were not sprayed during film formation, so the pore sizes on their surfaces were small, such as Fig. 9 As shown, the surface has no pores, resulting in a smaller flux, while the membrane surfaces of S1 to S4 have clear pores, so the flux is larger, but the retention rate is also close to 100%. This is because the surface pore structure of membranes S1 to S4 is uniform, and the formed network structure makes the internal separation performance better.
[0125] As the content of nanoparticles on the dry PVDF membrane increases, the flux of the membrane decreases, and the salt retention rate remains almost unchanged. Compared with the nanoparticle composite spray membrane, its flux is lower; but the retention rate of the C1 membrane is higher than that of the S1 membrane, reaching 99.64%. This is because the C1 membrane is based on the C0 membrane, the C0 membrane has a smaller pore size, and the membrane mass transfer resistance is larger, resulting in a smaller flux and a larger salt retention rate.
[0126] The present invention further selected S3 and S4 membranes with comparable flux and better interception performance for long-term membrane distillation test and compared them with C0 membrane. Fig.19 As shown. Within 50 hours, both S3 and S4 membranes maintained a retention rate of more than 99.99%, and the flux was also maintained at more than 60% of the initial flux. The flux of the S3 membrane is basically greater than that of the S4 membrane. This is because the pore size and porosity of the S3 membrane are slightly larger than those of the S4 membrane, and the thickness of the membrane is also smaller, which makes the flux of S3 slightly larger than that of S4. It can be seen that the flux of the membrane decreases slowly during long-term operation and maintains a high salt retention level. This is attributed to the superhydrophobicity of the membrane surface and the less wetting of the membrane. At the same time, due to the superhydrophobicity of the S4 membrane, its salt retention within 50 hours is better than that of the S3 membrane. The flux and retention rate of the C0 membrane are smaller than those of the S3 and S4 membranes. The smaller pore size of the base membrane makes the flux of the C0 membrane smaller. During the initial measurement, due to the smaller pore size of the C0 membrane, the salt retention rate was not much different from that of the S3 and S4 membranes. However, due to its lower hydrophobicity, as the detection time increased, membrane pore wetting gradually occurred, resulting in a significant decrease in its salt retention rate, which ultimately failed to meet the salt retention rate requirements in the water treatment process.
[0127] In order to further detect the contamination and wetting of the membrane, the S3 membrane with good VMD performance was tested for 10 hours and circulated and cleaned with deionized water through a cross-flow filtration device until the conductivity of the circulating water no longer changed, which was considered to be the completion of membrane surface cleaning. Fig. 20 As shown, Fig. 20 (a) shows the SEM morphology changes of the whole process. After 10 h of VMD operation, some salt crystals covered the membrane surface, especially on the nanoparticles. This shows that there is still slight membrane contamination due to the concentration polarization on both sides of the membrane. Fig. 20 As shown in (b), after 10 h of operation, the flux increased from the initial value of 20.31 kg·m -2 ·h -1 Reduced to 18.23 kg·m -2 ·h -1 After deep cleaning with deionized water, the salt crystals on the membrane surface were washed away and the flux was restored to 19.47 kg·m -2 ·h -1 ,The super hydrophobicity of the membrane surface makes the membrane flux less affected by pollution and the retention rate remains at a high level.
[0128] In summary, the superhydrophobic membrane of the present invention exhibited a steam flux comparable to that of the membrane S0 sprayed with ethanol and a salt retention rate of up to 99.99% in the vacuum membrane distillation experiment, while being able to maintain high flux and high retention for a long time; the existing membrane contamination can also be alleviated by deep cleaning with water to achieve flux recovery.
[0129] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a PVDF super-hydrophobic membrane, characterized in that: It is a non-solvent composite spray synergistic phase transformation method, which specifically includes the following steps: S1. Preparation of modified F-SiO2 nanoparticles: Dispersing hydrophilic silica nanoparticles in a solvent, stirring and ultrasonically dispersing the particles to form a suspension, adding sodium methyl silicate to the suspension and continuing to stir, then adding PFDTES and TEOS, mechanically stirring and reacting for a period of time, hydrolyzing and co-condensing to obtain modified hydrophobic F-SiO2 nanoparticles, washing and drying for later use; S2. Prepare PVDF casting solution: dry PVDF powder, mix with solvent triethyl phosphate (TEP), seal and put into an oven, shake the casting solution in time to ensure uniform dissolution, and obtain a uniform and transparent casting solution; S3, preparing a spraying liquid: uniformly dispersing the modified F-SiO2 powder obtained in step S1 in anhydrous ethanol, and uniformly dispersing by ultrasonication; S4, preparing a PVDF super-hydrophobic membrane: casting the casting solution prepared in step S2 on a non-woven fabric, coating it to obtain a new membrane, and then immediately spraying the spraying solution prepared in step S3 onto the surface of the new membrane with a spray gun, immersing the sprayed membrane in a deionized water coagulation bath at room temperature for at least 12 hours to complete the phase inversion process, and finally drying it under ambient conditions to obtain the PVDF super-hydrophobic membrane.
2. The method for preparing a PVDF super-hydrophobic film according to claim 1, wherein In the step S1, the solvent is a mixed solvent of water and ethanol, and the volume ratio of water to ethanol is 1:(2-50).
3. The method for preparing a PVDF super-hydrophobic film according to claim 1, wherein In the step S1, the amount ratio of the silicon dioxide nanoparticles, sodium methyl silicate, PFDTES and TEOS is (1-10): (1~10):(1~10):(1~10)。 4. The method for preparing a PVDF super-hydrophobic film according to claim 1, wherein In the step S2, the mass ratio of the PVDF powder to the TEP solvent is 1:(3-10).
5. A method for preparing a PVDF super-hydrophobic film according to claim 1, characterized in that, In the step S3, the mass percentage of the modified nanoparticles in the spraying liquid is 0.1% to 1.5%.
6. A method for preparing a PVDF super-hydrophobic film according to claim 5, characterized in that, The prepared spraying liquids include four kinds, in which the mass percentages of the modified nanoparticles are 0.1wt%, 0.5wt%, 1.0wt% and 1.5wt% respectively.
7. A method for preparing a PVDF super-hydrophobic film according to claim 1, characterized in that, In step S4, the spray gun is connected to a small air pump to perform a spraying operation at a working pressure of 2 bar.
8. A method for preparing a PVDF super-hydrophobic film according to claim 1, characterized in that, The water contact angle of the modified F-SiO2 prepared in step S1 is higher than 150°.
9. A PVDF super-hydrophobic membrane, characterized in that: The non-solvent composite spray synergistic phase transformation method is used to prepare the product.
10. A PVDF super-hydrophobic membrane according to claim 9, characterized in that: The super hydrophobic membrane has high roughness and low surface energy, a water contact angle higher than 150.75°, a maximum salt retention rate of 99.99%, and a flux of 18.21 kg·m -2 ·h -1 above.
Citation Information
Patent Citations
Semi-crystalline polymer film
CN115835918A
Method for preparing fully hydrophobic film in one step through electrostatic synergism and spraying-assisted phase separation
CN117717905A
Scale inhibition slurry as well as preparation method and application thereof
CN118325402A
Super-hydrophobic anti-corrosion luminous coating, preparation method and application
CN118685101A
Polyvinylidene fluoride porous flat membrane and method for manufacturing the same
JP2012139619A
Cited By
Method for preparing super-hydrophobic membrane through silane-assisted non-solvent induced phase separation, super-hydrophobic membrane and application
CN122006506A
A method for preparing a super-hydrophobic film by silane-assisted non-solvent induced phase separation, a super-hydrophobic film and applications thereof
CN122006506B